2013
DOI: 10.1103/physrevlett.111.125501
|View full text |Cite
|
Sign up to set email alerts
|

Embedding Quasicrystals in a Periodic Cell: Dynamics in Quasiperiodic Structures

Abstract: We introduce a construction to "periodize" a quasiperiodic lattice of obstacles, i.e., embed it into a unit cell in a higher-dimensional space, reversing the projection method used to form quasilattices. This gives an algorithm for simulating dynamics, as well as a natural notion of uniform distribution, in quasiperiodic structures. It also shows the generic existence of channels, where particles travel without colliding, up to a critical obstacle radius, which we calculate for a Penrose tiling. As an applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…Therefore, we expect weak super-diffusion if the obstacles are small enough, which agrees with numerical results founded in [26]. However, the numerical results are not completely convincing, especially when the obstacles are very small.…”
Section: A Generic Existence Of Channels In Quasiperiodic Lorentz Gasessupporting
confidence: 77%
See 3 more Smart Citations
“…Therefore, we expect weak super-diffusion if the obstacles are small enough, which agrees with numerical results founded in [26]. However, the numerical results are not completely convincing, especially when the obstacles are very small.…”
Section: A Generic Existence Of Channels In Quasiperiodic Lorentz Gasessupporting
confidence: 77%
“…There are several methods to produce quasiperiodic arrays, not all of which producing the same tiling [56]; one of the most popular is the projection method [29,57,58]. Reversing this method, it is possible to simulate and analyze the dynamics of a quasiperiodic LG as a periodic billiard, as two of the current authors previously showed [26]. Throughout this paper, we take the interaction potential to be that of the hard sphere.…”
Section: A Lorentz Gasmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, spatial symmetries hold strictly only locally rather than globally in real systems. There are in fact many scenarios where a system is naturally made up of different domains in which distinct spatial symmetries hold locally, striking examples being quasicrystals [12][13][14] or large molecules [15,16]. The quest of finding symmetry remnants in stationary states of systems with globally broken but locally retained symmetries recently led to a generic treatment of one-dimensional (1D) local symmetries in terms of invariant two-point currents [17].…”
mentioning
confidence: 99%